(untitled) (Universitas Medica, 2021)
Nausea and vomiting (NaV) are two of the adverse effects frequently associated with the administration of chemotherapy in addition to other drugs used in hematology. The importance that the prevention and management of these symptoms has in our patients, lies in the risks they represent when they are not treated correctly, such as: dehydration, hydroelectrolytic disorders and acute renal failure. For the preparation of this article, a review of the literature was carried out based on the evidence and available schemes for the prevention and treatment of NV induced by medications used in the management of patients with hematological pathologies.